Bengali Female Migrants: Domestic Workers in Mumbai. Issue 2 (December 2018) - Banerjee, Snigdha; Govil, Dipti
Female domestic workers are part of the unorganized workforce in India. This trend of keeping women as domestic workers has increased day by day and could be because of lack of education, unemployment and lack of other vocational skills. This article is based on a primary survey in two slums of Mumbai. It highlights the life and living experiences of Bengali female migrants as domestic servants in Mumbai. It reveals their socio-economic status before and after migration and advocates the analysis of female migratory processes and involvement in the urban informal labour sector. It also explores the working conditions and discrimination faced by female migrants at the workplace. Their experiences would illustrate not only the issues faced by domestic workers but also the limitations of the informal labour sector altogether.